UTILIZATION OF CASSAVA WASTE IN THE PRODUCTION OF PLYWOOD ADHESIVE EKSTENDER WITH DEXTRIN (WITH ACID CATALYST) - Rukmini, Piyantina (Universitas Lambung Mangkurat, 2017)
Abstract- Require of manihot Esculinta Crantz in Indonesia rises in every year as growth of Indonesian people, bioethanol industry,and animal food. Raw material that use in this research is cassava wastes. This research aimed to know the utilization of cassava waste, the optimum condition process of dextrin, and to know the variable that influent the utilization of cassava waste in the production of adhesive ekstender ( catalyst concentration and time). The dekstrin process need beaker glass, stirrer, electric stove with oilbatch heater, thermometer, screening 80 mesh. Cassava wastes that keep on several days is burned without water at 800 C for 1 hours. Then drops acid catalyst ion the beaker glass with different concentration. Then the temperature is raised until 1100C for 1 hour. After the drying process, make it cool then screen it in to screener 80 mesh. The results show that on the higher concentration of acid, dextrin will get on the higher concentration. At the certain concentration of acid, dekstrin will not get in the high concentration. Maximum efficiency of the concentration of acid is 0,8 N. Keeping long day for cassava waste can make lower the concentration of dextrin. The best keeping day is the first day until four day. Keywords: Cassava waste, dextrin, ekstender, wood adhesion